2021
DOI: 10.52158/jacost.v2i2.177
|View full text |Cite
|
Sign up to set email alerts
|

Uji Plagiarism pada Tugas Mahasiswa Menggunakan Algoritma Winnowing

Abstract: Plagiarism is the act of taking or plagiarizing the work, ideas or ideas of others either intentionally or unintentionally and claiming to be one's own work without mentioning the source or author. Often students plagiarize assignments given by the lecturer so that sometimes students just copy other people's assignments to complete the assignment. So that this can lead to dependence on other people in doing assignments and not being able to independently carry out assignments given by the lecturer. Currently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
0
0
2
Order By: Relevance
“…Membangun sebuah sistem yang dapat melakukan pengecekan kesamaan judul tugas akhir untuk mencegah kegiatan plagiarisme, dibutuhkan metode untuk proses pengecekan plagiarisme tersebut. Algoritma winnowing adalah salah satu algoritma yang dapat melakukan metode dokumen fingerprinting untuk mendeteksi plagiarisme [1]. Document fingerprinting merupakan metode yang digunakan untuk mendeteksi keakuratan salinan antar dokumen atau hanya sebagian teks saja dengan prinsip kerja menggunakan teknik hashing [2].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Membangun sebuah sistem yang dapat melakukan pengecekan kesamaan judul tugas akhir untuk mencegah kegiatan plagiarisme, dibutuhkan metode untuk proses pengecekan plagiarisme tersebut. Algoritma winnowing adalah salah satu algoritma yang dapat melakukan metode dokumen fingerprinting untuk mendeteksi plagiarisme [1]. Document fingerprinting merupakan metode yang digunakan untuk mendeteksi keakuratan salinan antar dokumen atau hanya sebagian teks saja dengan prinsip kerja menggunakan teknik hashing [2].…”
Section: Pendahuluanunclassified
“…Berikut persamaan untuk rolling hash: 𝐻(𝑐1 … . π‘π‘˜) = c 1 * 𝑏 (π‘˜βˆ’1) + c 2 * 𝑏 (π‘˜βˆ’2) + β‹― + 𝑐 (k-1) * 𝑏 (π‘˜) + 𝑐 (k) π‘šπ‘œπ‘‘ π‘ž (1) Keterangan: H: substring c: nilai ascii per-karakter b: konstan bilangan prima k: banyak karakter q: module bilangan prima…”
Section: ) Perhitungan Fungsi Hash Untuk Setiap N-gramunclassified
“…The value of the k and w parameters dramatically influences the resulting similarity value. Research conducted by [5] by comparing two random assignments and obtaining various similarity values. The greater the value of k and w, the smaller the resulting similarity value; the smaller the k and w value, the greater the resulting similarity value.…”
Section: Introductionmentioning
confidence: 99%
“…Research by [5] used the winnowing algorithm to detect plagiarism in programming source code by using ten student assignments using the winnowing algorithm and obtaining various similarity values by comparing two tasks randomly. And it can be concluded that the parameter values k and w significantly affect the resulting similarity value, namely the greater the k and w value, the smaller the resulting similarity value, and the smaller the k and w value, the greater the resulting similarity value.…”
Section: Introductionmentioning
confidence: 99%